Peran Bahasa dalam Penerapan Ilmu Pengetahuan - Yuni Revita; Sufyarma Marsidin; Sulastri Sulastri (Journal on Education, 2023)
Education and Science is a unit that is needed by everyone to broaden their thinking. Language is a sound or speech symbolization system in human daily communication. For humans, there are two roles that language has, namely as a medium of thought and as a medium of communication. The thinking process cannot be separated from language mastery because humans think through language symbols. Human thoughts and ideas are very important to convey to others. Good communication must use good media as well. Language plays an important role in the development of knowledge, especially as a medium of thought and a medium of communication. Language should be able to explain and represent the symbolism of a concept in science itself. Vocabulary is the treasure of a language, especially those that are closely related to messages that connote thoughts. The preparation of this analysis uses a term known as a literature review study or literature review from various scientific journals and Google Scholar to obtain relevant journal articles. The aim of this type of research is to incorporate relevant theory and ongoing or previously unknown issues as building blocks for the analysis of research results. Seeing the interconnectedness of the sources for this theoretical study, it can be concluded that language has a very important role in the application of knowledge, because language itself has a very close attachment/relationship with the mind. Language is a medium of thinking and a medium of human communication.